Pengaruh Karakteristik Syariah Marketing terhadap Kepuasan Nasabah Bank Syariah Indonesia KFO Mikro Merlung - Hana Lukiana; Usdeldi Usdeldi; Muhamad Subhan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This research is motivated by the current rapid development of Islamic Banking, causing the banking industry to face a very competitive business environment. Therefore, approaches and breakthroughs are needed to develop the Islamic market in indonesia. Therefore, one of the efforts of Islamic Banks is to implement Islamic Marketing which consists of fou characteristics, namely Theistic, Ethical, Relistic and Humanistic, which is a business process whose entire process applies islamic values.This study aims to determine whether the syariah marketing variables consisting of Theistic, Ethical, Realistic and Humanistic have a simultaneous or partial effect on Customer Satisfacion at Bank Syariah Indonesia KFO Mikro Merlung. This test uses a quantitative research method with an associative research type and uses a questionnaire and observation method. The questionnaire is used to obtain data on the characteristics of respondents, namely customers and to obtain data on the influence of syariah marketing on customer satisfaction at Bank Syariah Indonesia KFO Mikro Merlung through statements in the questionnaire. While observation is used for direct observation of the research location and to dig up data on organizational structure, population an samples.The results of this study indicte that the independent variables of Syariah Marketing consisting of Theistic, Ethicl, Realistic and Humanistic have a simultaneous effect on satisfaction of Bank Syariah Indonesia KFO Mikro Merlung with an effect of 40%, while the remaining 60% is explained by other variables not examined in this study, partially, it is concluded tht of the four characteristics there are there are three variables that have a significant effect on customer satisfaction, namely Theistic, Ethical, and Humanistic while the Realistic variable has an effect but is not significant on customer satisfaction of Bank Syariah Indonesia KFO Mikro Merlung.